Providers' Perceptions of Trauma-Focused EBT/EBP Implementation Fidelity: Implementation Process and Individual Influences. - Gusler, Stephanie; Sprang, Ginny; Eslinger, Jessica; Whitt, Adrienne (Community Mental Health Journal, 2026)
Implementation fidelity is the extent to which an intervention is delivered in the manner in which it was designed. Within randomized-controlled trials (RCTs), fidelity is often rigorously ensured through strategies out of reach for most organizations. This limitation may be of particular concern for trauma-focused evidence-based treatments/evidence-based practices (EBT/EBPs), as the needs of individuals and families seeking trauma-based treatment are often complex, with existing comorbidities that can complicate recovery. The present study used the Consolidated Framework for Implementation Research (CFIR) to examine implementation process and individual characteristics, as well as interactions among these factors in impacting provider's perceptions of fidelity. Data came from 598 primarily child serving mental health providers, who completed an online survey regarding provider demographics, perceptions of personal effectiveness, work experiences such as secondary traumatic stress (STS) and compassion satisfaction, and organizational implementation strategies used for a trauma-focused EBT/EBP. Significant positive associations were found between perceptions of implementation fidelity and compassion satisfaction, implementation strategy use, and personal effectiveness. Further, STS was significantly negatively associated with implementation fidelity. Significant differences were found based on population served and use of consultation calls and in-person supervision. Within a regression model, a significant two-way interaction between STS and implementation strategy use was significant, along with a three-way interaction between STS, implementations strategy use, and personal effectiveness. This study advances our understanding of how fidelity is created, maintained and understood in implementation settings that provide EBT/EBPs to individuals exposed to trauma.